Alley farming research at the International Institute of Tropical Agriculture (IITA) - Osiname, O.; Tonye, J. (1994)
Alley agriculture in Africa. In Alley cropping, food crops are grown in alleys formed by hedgerows of trees or shrubs, preferably legumes. The hedgerows are cut back at planting and at intervals during cropping to provide mulch and manure for crops growing in the alleys, and to prevent shading and to reduce competition with associated food crops. The incorporation of small ruminants production by the International Livestock Center in Africa (ILCA) (Okali and Sumberg, 1985) into the alley cropping system, using supplementary browse produced from the hedgerows on a cut and carry basis has led to the development of the alley farming concept. Alley farming can, therefore, be defined as an agroforestry system which seeks to exploit the potentials of multipurpose trees (MPTs) primarily for the maintenance of soil fertility and consequently for improved crop and livestock production.